Palaeogeografical and palaeoecological significance of the Uppermost Carboniferous and Permian rugose corals of Spitsbergen - Chwieduk, Edward (Wydawnictwo Naukowe UAM, 2013)
The Carboniferous and Permian rugose corals of the Cordilleran-Arctic-Uralian (C-A-U) Realm, belong to the best known group of animals of those periods. Spitsbergen, situated at that time on the northern margin of the drifting supercontinent Pangea, stands out from the entire C-A-U Realm for its exceptionally large accumulation of their fossils. The climate obtaining in the Carboniferous and Early Permian was favourable to their development. At that time today’s Svalbard Archipelago lay roughly just above the Tropic of Cancer and in those periods and later kept moving northwards until it had reached its present location between the 75th and 80th parallels in the northern subpolar zone. The corals described in this monograph come from three areas: the Hornsund region, a Polakkfjellet hill, and the Grønfjorden region. They belong to both, known and new species. Thus, on the one hand, they attest to the affi nity of the Spitsbergen rugosans with the rest of the C-A-U Realm, corroborating their connection with the faunas of Alaska, the Urals, the Central European Basin, and Arctic Canada (Sverdrup Basin). On the other hand, however, they can be indicative of limited communication possibilities, or perhaps of the presence on Spitsbergen environmental conditions determining such a taxonomic composition.
This research was financed by the State Committee for Scientific Research (KBN), project No. 0421/PO4/2003/24.
Keywords: Rugosa; Spitsbergen; Carboniferous; Permian